JavaScript and HTML5 at OSCON 2012. (O'Reilly, 2012)
"The sudden dominance of HTML5, JavaScript, and related technologies such as Node were hot topics at OSCON 2012. With this complete video compilation, you'll get more than a dozen JavaScript and HTML5 sessions presented at the conference. Learn about the latest trends from the experts, such as David Pacheco (Joyent), Scott Davis (ThirstyHead.com), Alice Boxhall (Google), and many more."--Resource description page.